Determination of Anxiety, Health Literacy and Belief Levels of Medication Use of Individuals with Chronic Diseases During The Covid-19 Pandemic Process - SOLMAZ, Gürcan (MAS Journal of Applied Sciences, 2023)
This study was conducted to determine the state-trait anxiety, health belief, and health literacy levels of individuals with chronic diseases during the COVID-19 pandemic. The study, which is a descriptive and relational type, was conducted with 207 chronic patients between July and September 2020. Data were collected with a personal information form, the Trait-State Anxiety Scale, the Health Literacy Scale, and the Health Belief Scale. The levels of trait and state anxiety, health belief, and health literacy are higher in females, university or higher education, single, good-income, comorbid disease, COVID-19 infected patients (p<.05). Participants aged 65 and over had the most elevated anxiety, lowest health belief, and health literacy mean scores (p<.05). In the study, a weak positive correlation was determined between the scales (p<.001). When the scores obtained from the trait anxiety, state anxiety, health belief, and health literacy scales were evaluated according to sociodemographic characteristics. Determining the anxiety, health literacy, and belief levels of individuals with chronic diseases and their influencing factors in extraordinary situations such as pandemics can provide effective management of the process and nursing care.